2009
DOI: 10.1667/rr1490.1
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Direct and Indirect Actions in Cell Killing by High-LET Radiations

Abstract: The biological effects of radiation originate principally in damages to DNA. DNA damages by X rays as well as heavy ions are induced by a combination of direct and indirect actions. The contribution of indirect action in cell killing can be estimated from the maximum degree of protection by dimethylsulfoxide (DMSO), which suppresses indirect action without affecting direct action. Exponentially growing Chinese hamster V79 cells were exposed to high-LET radiations of 20 to 2106 keV/mum in the presence or absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
104
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 40 publications
10
104
0
Order By: Relevance
“…McMahon et al, 2011a andLeung et al, 2011, simulated secondary electron emission from individual GNPs and postulated that local dose enhancement from short range Auger electrons mimicked the enhanced relative biological effect of heavy ions. With heavy ions, a comparable dose can be deposited to an equivalent dose of X-rays but the survival fraction of cells is much lower (Hirayama et al, 2009). The dose is localised to the ion-track and results in many more lethal double-strand breaks than the same dose spread homogenously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…McMahon et al, 2011a andLeung et al, 2011, simulated secondary electron emission from individual GNPs and postulated that local dose enhancement from short range Auger electrons mimicked the enhanced relative biological effect of heavy ions. With heavy ions, a comparable dose can be deposited to an equivalent dose of X-rays but the survival fraction of cells is much lower (Hirayama et al, 2009). The dose is localised to the ion-track and results in many more lethal double-strand breaks than the same dose spread homogenously.…”
Section: Discussionmentioning
confidence: 99%
“…(Bishayee et al, 2000) showed that DMSO protected cells from 125 I-and 131 I-iododeoxyuridine ( 125 IdU, 131 IdU) β-emitters, but not against 210 Po emitting 5.3 MeV α particles. Various experimenters have shown that DMSO can protect about 75% of the damage from X-rays (Hirayama et al, 2009, Shinohara et al, 1996. Interestingly, the degree of protection that DMSO affords high-LET radiation, depends on the energy (or LET) of the particle, with those near the Bragg peak imparting much more direct-action damage as one would expect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They will be required for the simulation of indirect effects of ionising radiation to DNA. Such effects are known to be dominant especially in the low LET domain (see for example Hirayama et al [43]). …”
Section: Water Radiolysis Modellingmentioning
confidence: 99%